The herbage productivity of tall fescue in the Pampas region of Argentina is correlated to its ecological niche - Scheneiter, Jorge Omar (2016)
Since its introduction in the 1950s, tall fescue has spread throughout the Pampas region of Argentina to become naturalized in much of this region. Its annual forage mass productivity shows significant differences among sites. In this work, we hypothesized that, under dryland conditions, the annual forage mass productivity is related to the probability that the corresponding site is within the ecological niche of the species. To test this hypothesis, the spontaneous occurrence of tall fescue was surveyed in an area of 440 000 km2. The abundance of tall fescue was verified on roadsides of national and provincial roads, in systematic sampling points spaced every 50 km. Subsequently, the ecological niche of the species was estimated with the Maxent software, based on the environmental information available. Additionally, the bioclimatic variables with greatest influence in determining the ecological niche were identified. Based on the information of comparative yield trials of tall fescue cultivars, a correlation analysis between annual forage mass productivity and the likelihood of ecological niche was performed. We found that the realized ecological niche of tall fescue in the Pampas region covers an area of 237 000 km2 where the average minimum temperature of the coldest month is between 2_6 and 3_2°C and the rainfall in the driest quarter is 100 mm or higher. We also found that there were significant correlations between annual forage mass productivity and the probability of realized ecological niche. Therefore, in areas with low probability of realized ecological niche, other forage species could be a better option than tall fescue to obtain a high and stable annual forage mass productivity.